PERTUMBUHAN LONGKIDA (Nauclea orientalis L) DENGAN PEMBERIAN TANDAN KOSONG KELAPA SAWIT(TKKS) PADA REKLAMASI PASCATAMBANG BATUBARA - Catur Cahyadi; Yudi Firmanul Arifin; Fakhrur Razie; Akhmad Rizalli Saidy (EnviroScienteae, 2023)
Oil palm empty bunches can improve fertility and soil nutrient on ex-mining land. This study aimed to evaluate the effect of oil palm empty fruit bunches on growth of Longkida (Nuclea orientalist L) on post-mining land. This research was conducted at field for 6 months. The application was done at new plant . A single factor of oil palm empty fruit bunch organized on 4 treatments and 10 replication. The results showed oil palm empty bunches able to increase growth of Longkida . Base on data giving 15 kg of EFB has a significant effect in increasing the growth of longkida which can be seen from stem height growth of 160%, stem diameter growth of 421% and leaf number growth of 489% in 6 months beginning.